Influence of Chain Length of Gradient and Block Copoly(2‐oxazoline)s on Self‐Assembly and Drug Encapsulation (Small 17/2022). Issue 17 (27th April 2022) - Sedlacek, Ondrej; Bardoula, Valentin; Vuorimaa‐Laukkanen, Elina; Gedda, Lars; Edwards, Katarina; Radulescu, Aurel; Mun, Grigoriy A.; Guo, Yong; Zhou, Junnian; Zhang, Hongbo; Nardello‐Rataj, Véronique; Filippov, Sergey; et al.
Abstract : Amphiphilic Gradient Copolymers In article number 2106251, Richard Hoogenboom and co‐workers provide an in‐depth analysis of micelles based on amphiphilic gradient poly(2‐oxazoline)s with different chain lengths to evaluate their potential for micellar drug delivery systems and compare them to the analogous diblock copolymer micelles. In addition to several interesting differences between the two copolymer architecture classes, it can be concluded that gradient copolymers provide stable nanoformulations with comparable drug loadings to block copolymer systems and benefit from more straightforward copolymer synthesis.